2012
DOI: 10.1111/j.1553-2712.2012.01328.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Exception From Informed Consent Regulations in a Large Multicenter Emergency Clinical Trials Network: The RAMPART Experience

Abstract: Clinical trials investigating therapies for acutely and critically ill and injured patients in the earliest phases of treatment often can only be performed under regulations allowing for exception from informed consent (EFIC) for emergency research. Implementation of these regulations in multicenter clinical trials involves special challenges and opportunities. The Rapid Anticonvulsant Medication Prior to Arrival Trial (RAMPART), the first EFIC trial conducted by the Neurological Emergencies Treatment Trials (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 10 publications
1
28
0
Order By: Relevance
“…This is in contradiction with some current rules that would allow a waiving of consent for observational studies [29]. The suggested requirement for dual consent in which one person should be the family or ICU doctor might be a solution regarding the exceptional and specific circumstances of emergencies [30,31]. Our results were also consistent with literature in which between 50 and 86 % of respondents accepted deferred consent [22,32,33].…”
Section: Discussionsupporting
confidence: 47%
“…This is in contradiction with some current rules that would allow a waiving of consent for observational studies [29]. The suggested requirement for dual consent in which one person should be the family or ICU doctor might be a solution regarding the exceptional and specific circumstances of emergencies [30,31]. Our results were also consistent with literature in which between 50 and 86 % of respondents accepted deferred consent [22,32,33].…”
Section: Discussionsupporting
confidence: 47%
“…Two sites reported using random-digit dialing surveys, and 3 sites conducted large surveys at public events or Emergency Departments. Aggregated, network-wide estimates of the total numbers of each type of event and numbers of participants have been previously reported (8). …”
Section: Resultsmentioning
confidence: 99%
“…Generating interest and finding individuals willing to talk about a study appear to be major challenges, as evidenced by the fact that 21 such events previously reported across the network involved only 256 participants (8). In contrast, respondents found attending existing meetings (particularly of seizure support groups) more productive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The case studies presented here are cases reported to the HSWG for discussion of ethical challenges that arose during the conduct of the ProTECT-III trial. The cases present the complexities of consent by an LAR within the context of an EFIC study.…”
Section: Introductionmentioning
confidence: 99%